Note su RRC 442: Archagathus e la propaganda degli Acilii Glabriones - Di Jorio , Francesco (KOINON: The International Journal of Classical Numismatic Studies, 2024)
This article suggests a different interpretation of RRC 442, issued by M. Acilio Glabrione, proposing that the design is a form of propoganda linked to the gens of the moneyer.